Aplikasi Fissure Sealant untuk Mencegah Terjadinya Karies Dini Pada Anak Sekolah Dasar Negeri 05 Palembang - Mujiyati M; Sri Wahyuni; Masayu Nurhayati (Yayasan Daarul Huda Kruengmane, 2025)
The maintenance of oral and dental health must receive special attention from both teachers at school and parents at home. Most elementary school–aged children are still dependent on their parents, especially their mothers, for the maintenance of their dental health. At school, it is advisable for every school to have a School Dental Health Program (UKGS) that can help monitor students’ dental health. One indicator of human quality of life is health.The purpose of this community service activity is to improve a person’s oral and dental health, one of which is by preventing the occurrence of dental caries through providing education about the benefits of applying fissure sealant materials to tooth surfaces that have deep pits and fissures. Prevention using fissure sealants is especially appropriate for the first permanent molars that erupt at the age of 5–6 years. At this age, children do not yet understand how to properly maintain oral and dental hygiene, including correct toothbrushing techniques. Therefore, information about the application of fissure sealants to prevent early caries is very important to be conveyed to children, especially to teachers in elementary schools. The expected outcome after this community service activity is an increase in children’s knowledge about how to prevent early dental caries through the application of fissure sealants.